The 2008-09 Global Financial Crisis: Services to the Rescue in Malaysia - Sieh Lee, Mei Ling (Asian Journal of Business and Accounting, 2017)
Conventional approaches of increasing public expenditure on economic sectors and on social infrastructure construction for the purpose of boosting demand and stimulating multiplier effects continued to be important in the global financial crisis of 2008-09. In most Asian countries that were negatively impacted, largely because of their reliance on the US market where the problems started, the Keynesian path was followed along with other actions. The economic stimulus packages executed by Malaysia included numerous policy measures within the services sector. They reflected the changing economic structure and understanding of evolving needs. Various services subsectors have assumed significance not only as avenues for economic growth in prosperous years, but also as important avenues for buffering and correcting the debilitating effects of the recession. There is a need among developing economies, such as Malaysia, to identify gaps to develop and strengthen the capabilities of monetised services activities for playing a bigger role in times of future economic challenges. Keywords: Economic Crisis, Policy Intervention, Services Recovery Measures